2001
DOI: 10.1668/0003-1569(2001)041[1057:oocrp]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of Crustacean Respiratory Proteins1

Abstract: SYNOPSIS. The respiratory proteins hemoglobin and hemocyanin share the function of oxygen transport, but the proteins belong to separate gene families, and their active sites and the metal ions that bind the oxygen differ. Either hemoglobin or hemocyanin, but not both, is expressed in the hemolymph of many arthropod crustaceans. Hemoglobin is present in Branchiopoda, Ostracoda, Copepoda, rhizocephalan Cirripedia and one suborder of amphipodan Malacostraca, while hemocyanin has been described in Malacostraca. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In contrast, Wolf et al [64] found evidence for haemocyanin in extracts of eggs and embryos (larger than 0.5 mm in mantle length) using immunoelectrophoresis. In vertebrates, a developmental shift of the respiratory protein is well studied [40,41] and also for invertebrates it has already been described [31,37,38]. Yet Sepia officinalis represents the only mollusc for which an embryonic form of haemocyanin has been published.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Wolf et al [64] found evidence for haemocyanin in extracts of eggs and embryos (larger than 0.5 mm in mantle length) using immunoelectrophoresis. In vertebrates, a developmental shift of the respiratory protein is well studied [40,41] and also for invertebrates it has already been described [31,37,38]. Yet Sepia officinalis represents the only mollusc for which an embryonic form of haemocyanin has been published.…”
Section: Discussionmentioning
confidence: 99%
“…Besides adaptation to changing environmental conditions, different isoforms of respiratory proteins are also known to be expressed during the course of ontogeny (Crustaceans [31], Cancer magister and C. productus [32-35], Artemia salina [36], Schistocerca americana [37], Chironomus plumosus and Chironomus thummi [38,39], chicken [40] and mammals [41]). For example, humans start with the expression of embryonic haemoglobin, which is replaced by foetal, and afterwards by adult haemoglobin (e.g., [42]).…”
Section: Introductionmentioning
confidence: 99%